Conflitos entre a ação ergonômica e a percepção dos trabalhadores em uma central de teleatendimento - Santos, Carlos Eduardo dos (Universidade Federal de São Carlos, 2014)
This thesis aims to confront results of an ergonomic action taken by a company to improve working conditions with the perception and proposals of telemarketing operators, following a literature review and a case study. Concepts of Ergonomics and Ergonomic Work Analysis - EWA show the activity and constraints of the call center operator. Case study presents the ergonomic action taken by the company, its demand, realization strategy and policy recommendations. In field research, interviews were conducted with operators, monitors and supervisors to know their perception of work and difficulties faced. Literature shows that call center operators' work is exhausting and has a strong impact on mental factor, due to poor working conditions. Ergonomic intervention in this workplace becomes necessary in order to minimize impacts of the activity on the operators. It was observed that ergonomic action taken by the company and its policy recommendations are below the awareness of operators aiming for improvements in working conditions. Thus, one question is raised: do ergonomic actions really seek improvement of working conditions, or could it be only a decoy to demonstrate to supervisory institutions that measures are being taken?
CONFLICTS BETWEEN ERGONOMIC ACTION AND THE PERCEPTION OF WORKERS IN A TELEMARKETING CALL CENTER
Keywords: Ergonomia; Análise Ergonômica do Trabalho; Teleatendimento; Constrangimentos; Ergonomics; Ergonomic Work Analysis; Telemarketing; Constraints; CIENCIAS EXATAS E DA TERRA